Promoting relational thinking in preschoolers (ages 3–5) through participatory science learning: insights from RMTS with Roma children - Hristova, Penka; Koltcheva, Nadia; Mateeva, Antoaneta (Frontiers in Education, 2024)
The study examined the development of relational thinking in children aged 3–5 years within a Roma community using the relational matching-to-sample task. Following a four-month period of participatory science learning, there was a twofold increase in the proportion of relational choices made by the children. The teachers and assistant teachers deliberately encouraged child participation in science activities, while adhering to the established state curriculum. This emphasis on child involvement in science activities was discussed as a potential factor contributing to a domain-general shift in relational thinking, an effect not observed in the control group of children from the same community.